2019
DOI: 10.3390/jcm8101690
|View full text |Cite
|
Sign up to set email alerts
|

Vaso-Occlusion in Sickle Cell Disease: Is Autonomic Dysregulation of the Microvasculature the Trigger?

Abstract: Sickle cell disease (SCD) is an inherited hemoglobinopathy characterized by polymerization of hemoglobin S upon deoxygenation that results in the formation of rigid sickled-shaped red blood cells that can occlude the microvasculature, which leads to sudden onsets of pain. The severity of vaso-occlusive crises (VOC) is quite variable among patients, which is not fully explained by their genetic and biological profiles. The mechanism that initiates the transition from steady state to VOC remains unknown, as is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 67 publications
0
27
0
1
Order By: Relevance
“…In the course of a number of studies in humans using peripheral perfusion as a biomarker to understand the triggers of VOC, we have shown that cold, 8 mental stress, 5 respiration, 7 and pain itself, 4,23 all factors mentioned by patients to precede VOC, cause significant peripheral vasoconstriction, and that each study participant, both SCD and controls, seems to have a characteristic baseline vasoconstriction pattern that was observed over several experimental visits 6 . We suspected that individuals with high inherent vasoconstriction would have more frequent VOC 2 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the course of a number of studies in humans using peripheral perfusion as a biomarker to understand the triggers of VOC, we have shown that cold, 8 mental stress, 5 respiration, 7 and pain itself, 4,23 all factors mentioned by patients to precede VOC, cause significant peripheral vasoconstriction, and that each study participant, both SCD and controls, seems to have a characteristic baseline vasoconstriction pattern that was observed over several experimental visits 6 . We suspected that individuals with high inherent vasoconstriction would have more frequent VOC 2 .…”
Section: Discussionmentioning
confidence: 98%
“…While much of the literature in SCD has focused on nitric oxide (NO)‐mediated vascular dysfunction and cellular adhesion in the post‐capillary venules as key factors that may decrease microvascular flow and promote vaso‐occlusion, the role played by the sympathetic and parasympathetic nervous systems in causing vasoconstriction in the pre‐capillary arteriole, and decreasing microvascular flow has only recently been considered 3 . Our prior work has demonstrated that anticipatory pain, 4 experimental mental stress, 5 and cold exposure 6 all cause significant global vasoconstriction in SCD and non‐SCD controls and these responses vary significantly among all individuals 3 . Sighs (deep breaths) trigger peripheral vasoconstriction frequently in SCD but rarely in non‐SCD indivuals, 7 and cold face stimulation reduces the sensitivity of the baroreflex control of peripheral vascular resistance more in non‐transfused than transfused individuals with SCD or in controls 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This has been associated with increased risk of vaso-occlusive crisis and acute chest syndrome because of concomitant vasoconstriction, making sickling in clinically relevant blood vessels more likely. 8 In the same vein, given the association between hypertension and risk for CKD, 9 the same mechanisms of increased disease severity could be at play for the findings of increased ED length of stay for patients with kidney disease. Patients with kidney disease have worse SCD, as evidenced by end-organ damage caused by inflammation from high levels of hemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms that trigger VOC are still unknown, but recent research has suggested that autonomic dysfunction may play an important role. [1][2][3] We have been able to quantify blood flow and autonomic mediated vasoconstriction under different stimuli such as stress and cold. 1 Khaleel et al found that patients vasoconstricted in response to pain anticipation even before the actual pain stimuli.…”
Section: Aura and Mental Stress Are Associated With Reports Of Pain Imentioning
confidence: 99%
“…[1][2][3] We have been able to quantify blood flow and autonomic mediated vasoconstriction under different stimuli such as stress and cold. 1 Khaleel et al found that patients vasoconstricted in response to pain anticipation even before the actual pain stimuli. 3 In fact, clinically, patients have observed subtle differences in their body with no evidence of pain in the pre-pain phase.…”
Section: Aura and Mental Stress Are Associated With Reports Of Pain Imentioning
confidence: 99%